Pengaruh Vertical Garden Terhadap Suhu Ruangan Sebagai Lembar Kerja Materi Pemanasan Global - Widyawati Puji Lestari; Rini Rita T. Marpaung; Berti Yolida (Universitas Lampung, 2019)
This study aims to find out significant effect of vertical garden on air temperature in one of the classrooms and the characteristics of Student Worksheet (LKPD) in class VII of the application of the use of vertical garden in the material of global warming. The mining model used is Borg and Gall. The study was conducted at Bandar Lampung Middle School 8 in August-September 2018. The type of data used is quantitative data that were air temperature measurement data in the vertical garden and non-vertical garden spaces. The results showed the value of t way -2,226, because | z | ≥ t0.05 then H0 is rejected. This means that there way a significant effect of vertical garden on the temperature of the classroom, while for the average score characteristics (LKPD) by the lecturer and teacher validator based on the overall aspects of 85,45% and 77% with the category